Lateral Bearing Strength of Some More Species of Timber under 3.55 MM Dia (9 SWG) Common Wire Nails - Pruthi, K. S.; Punhani, R. K.; Singh, Jeet (Indian Forester, 1993)
Scientific studies on nailed joints have opened up new vistas for the wise and economic use of shorter lengths of planks/scantlings of secondary species in timber structures. As a pre-requisite to design, the lateral resistance to which nails are subjected by wood in structures has to be determined through laboratory tests. In this paper permissible nail-bearing strength in atleast 39 species for varied possible parameters are given along with their scope and application limitations.